Investigating the data science talent gap: Data practitioners’ perspectives - Wilma Coetzee; Roelien Goede (SA Journal of Human Resource Management)
Orientation: Data professionals are indispensable assets for companies, offering crucial insights that provide a competitive edge in economically demanding times.